A new dynamic model applied to electrically stimulated lower limbs and switched control design subject to actuator saturation and non-ideal conditions - Nunes, Willian Ricardo Bispo Murbak [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
Electrical stimulation is a promising technique for motor rehabilitation in cases of spinal cord injury. Stimulator saturation is important in the control system designs applied to electrical stimulation. The negligence of the actuator saturation in the electrical stimulation can lead to unwanted control results, which evidences the muscular fatigue effects. For the first time a switched controller subject to actuator saturation for electrically stimulated lower limb is proposed. The dynamic limb extension model is nonlinear and uncertain. The uncertain nonlinear system described by Takagi-Sugeno fuzzy models operating within an operating region in the state space is considered in this study. In addition, fault in the actuator, muscle activation uncertainty, and muscular non-idealities, such as fatigue, spasms, and tremor were considered at three three severity levels. The switched controller is compared to parallel distributed compensation technique. Simulations denote better results of the switched controller by dealing with parametric uncertainties. On the other hand, a challenge for FES control systems is to monitor torque in muscle contractions. In isotonic contraction applications, measuring torque is difficult. The novelty in this study is the proposal of a new nonlinear model, whose state variables are angular position, angular velocity and angular acceleration. In this new model the torque variable is replaced by the angular acceleration. Experimental tests list the parameters corresponding to 24 individuals (20 healthy and 4 paraplegic) for the linearized model using gray box identification approach.

A estimulação elétrica é uma técnica promissora para reabilitação motora em casos de lesão medular. A saturação do estimulador também é um requisito importante no projeto de sistemas de controle aplicados à estimulação elétrica. A negligência da saturação do atuador pode conduzir a resultados de controle indesejados, que evidencia os efeitos de fadiga muscular. Pela primeira vez é proposto um controlador chaveado sujeito à saturação para membro inferior estimulado eletricamente. O modelo dinâmico de extensão do membro inferior é não linear e incerto. O sistema descrito por modelos fuzzy Takagi-Sugeno e operando dentro de uma região de operação no espaço de estados é considerado neste trabalho. Além disto, falha do atuador, incerteza de ativação muscular, e não idealidades musculares, tais como fadiga, espasmos e tremor foram considerados em três níveis de severidade. O controle chaveado é comparado com a compensação distribuída paralela. Simulações denotam melhores resultados do controlador chaveado lidando com incertezas paramétricas da planta. Por outro lado, um desafio dos sistemas de controle para estimulação elétrica funcional é monitorar a dinâmica do torque em contrações musculares. Em aplicações de contração isotônica, medir o torque é algo difícil. A novidade neste estudo é a proposta de um novo modelo não linear, cujas variáveis de estado são posição angular, velocidade angular e aceleração angular. Neste novo modelo a variável torque é substituída adequadamente pela aceleração angular. Ensaios experimentais listam os parâmetros correspondentes a 24 indivíduos (20 saudáveis e 4 paraplégicos) para o modelo linearizado usando abordagem de identificação caixa cinza.
Novo modelo dinâmico aplicado a membros inferiores estimulados eletricamente e projeto de controle chaveado sujeito à saturação e condições não ideais
Keywords: Electrical stimulation; Paraplegics; Takagi-Sugeno fuzzy models; Linear matrix inequalities; Switched control; Estimulação elétrica; Paraplégicos; Modelos fuzzy Takagi-Sugeno; Desigualdades matriciais lineares; Controle chaveado